Financial Determinants of Corporate Social Performance: Empirical Evidence from Panel Data on Moroccan Listed Firms (2018-2023) - Benslama, Kaoutar; Ritahi, Oussama; Cadimi, Ikram; Malainine, Cheklekbire (International Journal of Economics and Financial Issues, 2025)
This study examines the financial determinants of corporate social performance (CSP) among firms listed on the Casablanca Stock Exchange over the period 2018–2023. Using balanced panel data and applying both Probit and Logit models, the analysis investigates whether profitability, financing capacity, firm size, and market valuation influence the likelihood of CSR engagement. The results reveal that return on equity (ROE) and return on sales (ROS) are consistently significant and positive drivers of CSP, while financial cash flows (CFF) also exert a positive influence in the Logit specification. Net income (RN) shows a marginal positive effect, suggesting that overall profitability supports CSR adoption, although less robustly. Conversely, earnings per share (EPS), return on assets (ROA), sales revenue (CA), and price-to-book ratio (P/B) do not significantly affect CSP in the Moroccan context. These findings highlight the central role of financial profitability and liquidity in enabling firms to allocate resources toward social responsibility. The study contributes to the literature by providing new evidence from an emerging economy, underscoring that in contexts where CSR practices are still developing, financial strength remains the key driver of responsible business conduct.